PROFESIONALISME GURU DALAM IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN DI SMKN 1 LHOKSEUMAWE - Nurasmah .; Murniati AR; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2015)
Abstract: This study aims to determine the understanding, implementation, and constraints faced by the teacher of Vocational High School State 1 Lhokseumawe in the implementation of the educational unit level curriculum. To achieve these objectives, this study uses descriptive qualitative approach. Data was collected through interviews, observation and documentation. The procedure of data analysis is data reduction, data display, and verification. While the subject of research is the principal, vice principal areas of curriculum and instruction, and teacher. The results showed that:(1) Teacher’s understanding of the educational unit level curriculum has been positive and keep up with the needs of learners with attention to the weaknesses of the development of science, technology, and art as a whole and sustainable; (2) Implementation of educational unit level curriculum is done by adjusting the curriculum with lesson plans grains so that the delivery of teaching materials has alignment with the time and abilities of students; and (3) Constraints teachers in the implementation of educational unit level curriculum, among others: (a) lack of educational facilities and infrastructure that support the application for the establishment of educational unit level curriculum perfectly, (b) lack of awareness of the teacher in preparing learning materials before the learning takes place, (c) the lack of allocation of time in learning process, and (d) the lack of teacher supervision in controlling the achievement of student learning outcomes in the classroom and in the school environment development.Keywords: Professionalism, Teacher, and Educational Unit Level Curriculum.Abstrak: Penelitian ini bertujuan untuk mengetahui pemahaman, implementasi, dan kendala yang dihadapi guru SMK Negeri 1 Lhokseumawe dalam implementasi KTSP. Untuk mencapai tujuan tersebut, penelitian ini mengunakan pendekatan kualitatif deskriptif. Teknik pengumpulan data dilakukan melalui wawancara, observasi, dan studi dokumentasi. Prosedur analisis data adalah reduksi data, display data, dan verifikasi. Sedangkan subjek penelitian adalah kepala sekolah, wakil kepala sekolah bidang kurikulum dan pengajaran, dan guru. Hasil penelitian menunjukkan bahwa: (1) Pemahaman guru terhadap KTSP sudah positif dan mengikuti perkembangan serta kebutuhan peserta didik dengan memperhatikan sisi kelemahan terhadap perkembangan ilmu pengetahuan, teknologi, dan seni secara menyeluruh dan berkesinambungan; (2) Implementasi KTSP dilakukan dengan menyesuaikan butir kurikulum dengan rencana pengajaran sehingga penyampaian materi ajar memiliki keselarasan dengan waktu dan kemampuan siswa; dan (3) Kendala guru dalam implementasi KTSP antara lain: (a) kurangnya sarana dan prasarana pendidikan yang mendukung untuk terwujudnya penerapan KTSP dengan sempurna, (b) kurangnya kesadaran guru dalam mempersiapkan materi pembelajaran sebelum pembelajaran berlangsung, (c) kurangnya pengalokasian waktu dalam proses pembelajaran, dan (d) kurangnya pengawasan guru dalam mengontrol hasil pencapaian prestasi belajar siswa di kelas dan perkembangannya di lingkungan sekolah.Kata kunci : Profesionalisme, Guru, dan KTSP